PENGARUH PERILAKU KONSUMEN TERHADAP MINAT BERKUNJUNG KE PANTAI SERANG KABUPATEN BLITAR - Najiyah, Virqotin; Fatmawati, Erlin Widya; Kurniastuti, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
Serang beach is one of the beaches in Blitar Regency. Visits to Serang Beach attractions are influenced by various factors. In this study the factors studied to determine the influence of visiting interest to Serang Beach is promotional factors, economic factors, factors of infrastructure and psychological factors. Sampling in this research is by accidental sampling method, in which the researcher has the freedom to choose who the consumer is met to be sampled, with the number of respondents as many as 100 people. Data analysis was done by using multiple linier regression analysis method, data processing was done by SPSS Statistics 16 for Windows program. The result of the research shows that promotion factor, economic factor, facility factor and psychological factors significantly (together) have an influence on the interest of visiting Serang Beach, and psychological factor is the most dominant factor influencing the interest to visit Serang Beach tourism object.